(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
It is difficult for service firms to envision and understand the aspectswhich mean high quality to consumers. Service quality allows an organization todifferentiate itself from the competitors and gain a substantial competitiveadvantage. Hence, service quality is at the forefront of both the marketingliterature in general and the service marketing literature in particular(Lassar et al., 2001). Qualityservice is recently considered a critical factor that enables many serviceorganizations achieve a differential advantage over their competitors. It hasbecome an important research topic because of its important relationship tocorporate marketing, financial performance, and moreover firm performance.